2004
DOI: 10.1152/ajprenal.00113.2003
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II-dependent increased expression of Na+-glucose cotransporter in hypertension

Abstract: Glucose uptake is increased in hypertension. Thus we investigated Na+-glucose cotransporter (SGLT2) activity and expression in proximal tubules from renovascular hypertensive rats. Sham-operated rats, aortic coarctation rats, and aortic coarctation rats treated with either ramipril (2.5 mg.kg-1.day-1 for 21 days) or losartan (10 mg.kg-1.day-1 for 21 days) were used. Na+-dependent glucose uptake was measured in brush-border membrane vesicles (BBMV). Vmax in BBMV from hypertensive rats was greater compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 31 publications
2
49
0
Order By: Relevance
“…In comparison, previously described antibodies against SGLT2 from different species did not reveal distinct immunochemical characterization of this protein (2,7,19,35,50). Our new antibody labeled a broad ϳ75-kDa protein band in Western blots of BBM or TCM isolated from the rat renal cortex and did not cross-react with rSGLT1 and rSGLT3, as indicated by the lack of reactivity with small intestine, where these transporters are expressed (5,16,38).…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…In comparison, previously described antibodies against SGLT2 from different species did not reveal distinct immunochemical characterization of this protein (2,7,19,35,50). Our new antibody labeled a broad ϳ75-kDa protein band in Western blots of BBM or TCM isolated from the rat renal cortex and did not cross-react with rSGLT1 and rSGLT3, as indicated by the lack of reactivity with small intestine, where these transporters are expressed (5,16,38).…”
Section: Discussionmentioning
confidence: 48%
“…Western blots and immunocytochemical studies using commercial polyclonal antibodies against SGLT2 have been reported. Whereas the antibodies allowed labeling of SGLT2-related bands in Western blots (7,18,35,42), the immunocytochemical studies did not reveal staining that allowed visualization of details (7).…”
mentioning
confidence: 98%
“…For example, recent studies demonstrated increased glucose reabsorption in proximal tubule membrane vesicles and increased expression of SGLT2 in response to renovascular hypertension in rats. Increased SGLT2 levels were also associated with chronic ANG II infusion (5). A study of GLUT1 expression in cultured mesangial cells showed that ANG II upregulated GLUT1 mRNA in a time-and dosedependent manner (26).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of the Na+/glucose cotransporter, SGLT1, at the proximal tubule was markedly increased in these animals. Enhanced glucose-dependent sodium transport has been reported in experimental hypertension, [33][34][35] and might represent one of the mechanisms involved in blood pressure elevation in this setting. Also consistent with the notion that hypertension in 3-month-old rats may be related to enhanced tubular sodium reabsorption is the observation that these animals showed a significant increase in the expression of the NBC located at the basolateral membrane of the proximal tubule.…”
Section: Discussionmentioning
confidence: 88%